Stories tell us? Political narrative, demes, and the transmission of knowledge through culture - Hartley, John (Routledge Taylor & Francis, 2015)
This paper compares two institutions of storytelling, mainstream national narratives and self-represented digital storytelling. It considers the centenary of World War 1, especially the Gallipoli campaign (1915) and its role in forming Australian ‘national character’. Using the new approach of cultural science, it investigates storytelling as a means by which cultures make and bind groups or ‘demes’. It finds that that demic (group-made) knowledge trumps individual experience, and that self-representation (digital storytelling) tends to copy the national narrative, even when the latter is known not to be true. The paper discusses the importance of culture in the creation of knowledge, arguing that if the radical potential of digital storytelling is to be understood – and realised – then a systems (as opposed to behavioural) approach to communication is necessary. Without a new model of knowledge, it seems we are stuck with repetition of the same old story.